In-situ Measurement of Three-dimensional Deformation Behaviour of Sheet and Tools During Stamping Using Borescope - Zamzuri, Hamedon; Mori, K.; Abe, Y. (Elsevier, 2014)
An in-situ measurement approach for three-dimensional deformation of sheet and tools during stamping using borescopes was developed. The borescope, consisting of a small CCD camera with a flexible cable, was connected to personal computer and placed inside a small space between the tool cavities to measure the deforming behaviour of the sheet. The deformation behaviour of the sheet and punch, the real springback and wrinkling in shrink flanging were measured. The deformed shape of the sheet measured by the borescope was in good agreement with that measured by the laser displacement sensor. In addition, three-dimensional deforming behaviour was measured by a stereoscopic method using two borescopes. It was found that the borescopes are effective in in-situ measurement of three-dimensional deformation behaviour of the sheet and tools.